Quantitative comparison of sink efficiency of Cu–Nb, Cu–V and Cu–Ni interfaces for point defects. (1st January 2015) - Mao, Shimin; Shu, Shipeng; Zhou, Jian; Averback, Robert S.; Dillon, Shen J.
Abstract: The efficacy of heterointerfaces as sinks for point defects in Cu was characterized using local measurements of tracer-impurity radiation-enhanced diffusion (RED). The measurements were performed as a function of irradiation temperature and Cu thickness in multilayer samples, with the results being compared to steady-state kinetic rate equations to determine sink strengths. Cu–Nb Kurdjumov–Sachs (KS) interfaces are found to be nearly ideal sinks for point defects, whereas Cu–Ni (1 1 1) heteroepitaxial interfaces are poor sinks; Cu–V KS interfaces are intermediate. Quantitative analysis of the RED data also yields the defect production efficiency for freely migrating defects in Cu, which is on the order of 1% for MeV Kr irradiation.